SLC2A5 overexpression in childhood philadelphia chromosome‐positive acute lymphoblastic leukaemia. (11th September 2018) - Zhao, Pan; Huang, Jingcao; Zhang, Dan; Zhang, Danfeng; Wang, Fangfang; Qu, Ying; Guo, Tingting; Qin, Yu; Wei, Jin; Niu, Ting; Zheng, Yuhuan
Summary: To study glycolysis/glycogenesis‐related genes expression in childhood B‐cell acute lymphoblastic leukaemia (B‐ALL), we performed a microarray‐based analysis using published gene expression profiles. We found that SLC2A5, which encodes solute carrier family 2 member 5 (SLC2A5, previously termed GLUT5) that facilitates cell fructose uptake, was up‐regulated in Philadelphia chromosome‐positive ALL (Ph+ALL). Microarray‐based analyses also suggested that SLC2A5 expression was significantly down‐regulated in childhood B‐ALL with t(1;19) or 11q23 mutation. High SLC2A5 expression was found in patients who had disease recurrence within 3 years, early relapse, shortened complete remission duration and positive minimal residue disease (MRD) status after treatment. SLC2A5 overexpression at both the mRNA and protein level in Ph+ALL was confirmed in a validation cohort of childhood B‐ALL. We also validated the correlation of SLC2A5 expression and MRD status. A mechanistic study using a human Ph+ALL cell line showed that BCR‐ABL1 kinase might regulate SLC2A5 expression via MYC. The tyrosine kinase inhibitors (TKIs) imatinib and dasatinib repressed SLC2A5 expression and the cell uptake of fructose. Fructose protected the tumour cells from nutrition deficiency and drug‐induced cell death. Overall, our findings showed that SLC2A5 was up‐regulated in childhood Ph+ALL. SLC2A5 expression correlated with childhood B‐ALL clinical factors, such as MRD status. Given that TKIs could inhibit SLC2A5 expression, repression of fructose utility after TKI treatment contributes to TKI‐induced Ph+ALL cytotoxicity. Targeting SLC2A5 might be promising in B‐ALL treatment, especially for Ph+ALL patients with high SLC2A5 expression.